1999
DOI: 10.1046/j.1471-4159.1999.720879.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mood‐Stabilizing Agents Lithium and Valproate RobustlIncrease the Levels of the Neuroprotective Protein bcl‐2 in the CNS

Abstract: Differential display of mRNA was used to identify concordant changes in gene expression induced by two mood-stabilizing agents, lithium and valproate (VPA). Both treatments, on chronic administration, increased mRNA levels of the transcription factor polyomavirus enhancer-binding protein (PEBP) 2␤ in frontal cortex (FCx). Both treatments also increased the DNA binding activity of PEBP2␣␤ and robustly increased the levels of bcl-2 (known to be transcriptionally regulated by PEBP2) in FCx. Immunohistochemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
273
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 456 publications
(283 citation statements)
references
References 21 publications
8
273
0
2
Order By: Relevance
“…Hence, we were unable to investigate the effect of longer chronic drug administration on gene expression. However, other groups have successfully maintained chronic administration of mood-stabilizing drugs in rats, 56,57 and as such, this may be a better therapeutic model for the future assessment of the differential expression of FAT and genes encoding its protein partners.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we were unable to investigate the effect of longer chronic drug administration on gene expression. However, other groups have successfully maintained chronic administration of mood-stabilizing drugs in rats, 56,57 and as such, this may be a better therapeutic model for the future assessment of the differential expression of FAT and genes encoding its protein partners.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used extensively to study the pharmacology of psychiatric medications. 7,40 The human prefrontal cortex, the post-mortem brain area under investigation here, has no known anatomical correlate in the rat brain. The approach here, therefore, was to examine the medication's effect in several different rat brain regions with the assumption that the changes that were found consistently in those regions would likely occur in the rat equivalent to the prefrontal cortex.…”
Section: Post-mortem Brain Tissue Analysismentioning
confidence: 97%
“…[3][4][5][6] Both medications have also been found to regulate biochemical processes involved in cellular protection. 7,8 Furthermore, in vivo magnetic resonance spectroscopy (MRS) of the brain has provided evidence for a neurotrophic/neuroprotective effect of lithium in patients. For example, lithium treatment has been shown to increase both gray matter density and levels of N-acetyl aspartate (NAA), a marker of neuronal viability, in the brain following chronic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report found that valproate also alters inositol metabolism by inhibiting myoinositol-1-phosphate synthase and causes inositol depletion by blocking de novo synthesis (Shaltiel et al, 2004). Manji and co-workers Chen et al, 1999b) have demonstrated in vivo that the apoptosis-inhibiting gene bcl-2 is induced both by lithium and valproate, assigning a potential neuroprotective role to these mood stabilizers. This group also reported that lithium treatment is associated with an increase in grey matter volume in patients (Moore et al, 2000).…”
Section: Introductionmentioning
confidence: 99%